Identification of a pathogenic founder variant in the WFS1 gene that causes Wolfram syndrome in the Druze population - Halabi, Inbal; Tenenbaum-Rakover, Yardena; Sagi-Dain, Lena; Koren, Ilana (Frontiers in Pediatrics, 2025)
ContextWolfram syndrome (WS) is an autosomal recessive neurodegenerative disorder caused by pathogenic variants in the WFS1 gene. It is characterized by central diabetes insipidus, juvenile-onset diabetes mellitus (DM), optic atrophy (OA), and deafness. The natural history of WS is variable, even within the same family and with the same variant.ObjectiveTo report the phenotypes of five patients of Druze origin, all carrying the same autosomal recessive pathogenic variant in the WFS1 gene.Patients & methodsFive patients belonging to three core families were enrolled. Clinical, biochemical, and genetic data were retrieved retrospectively from their medical files.ResultsAll five patients carried the same previously reported homozygous WFS1 pathogenic variant: c.2649del, p.Phe884fs. In all patients, the first presentation was DM at a mean age of 5.2 years (range 4–7), diagnosed initially as type 1 DM with negative anti-pancreatic autoantibodies, and all were treated with insulin by either pump or multiple injections. All five patients had OA that appeared at a mean age of 12.3 years (range 4–30). Three had hearing loss and neurological involvement, and none had diabetes insipidus. One patient was treated with a glucagon-like peptide 1 receptor agonist with a good response.ConclusionsThis is the first report of a founder pathogenic variant in the WFS1 gene in the Druze population in Israel. Our findings imply that molecular analysis is warranted in children presenting with DM and negative pancreatic antibodies. The identified variant should be considered for genetic testing in individuals of Druze ancestry diagnosed with young-onset non-autoimmune diabetes. Early diagnosis of WS is important for therapeutic approaches, especially since novel medications are becoming available.